Observations of strong ion-ion correlations in dense plasmas - Ma, T; Fletcher, L; Pak, A; Chapman, D; Falcone, R; Fortmann, C; Galtier, E; Gericke, DO; Gregori, G; Hastings, J; Landen, O; Le Pape, S; et al. (American Institute of Physics Inc., 2014)
Using simultaneous spectrally, angularly, and temporally resolved x-ray scattering, we measure the pronounced ion-ion correlation peak in a strongly coupled plasma. Laser-driven shock-compressed aluminum at ∼3× solid density is probed with high-energy photons at 17.9keV created by molybdenum He-α emission in a laser-driven plasma source. The measured elastic scattering feature shows a well-pronounced correlation peak at a wave vector of k=4Å-1. The magnitude of this correlation peak cannot be described by standard plasma theories employing a linear screened Coulomb potential. Advanced models, including a strong short-range repulsion due to the inner structure of the aluminum ions are however in good agreement with the scattering data. These studies have demonstrated a new highly accurate diagnostic technique to directly measure the state of compression and the ion-ion correlations. We have since applied this new method in single-shot wave-number resolved S(k) measurements to characterize the physical properties of dense plasmas. © 2014 AIP Publishing LLC.